2010
DOI: 10.1002/humu.21245
|View full text |Cite
|
Sign up to set email alerts
|

Predicting functional significance of cancer-associated p16INK4a mutations in CDKN2A

Abstract: Inherited mutations affecting the INK4a/ARF locus (CDKN2A) are associated with melanoma susceptibility in 40% of multiple case melanoma families. Over 60 different germline INK4a/ARF mutations have been detected in more than 190 families worldwide. The majority of these alterations are missense mutations affecting p16INK4a , and only 25% of these have been functionally assessed. There is therefore a need for an accurate and rapid assay to determine the functional significance of p16INK4a mutations. We reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 50 publications
5
38
0
1
Order By: Relevance
“…44 The other mutations were described with evidence of pathogenicity. [45][46][47][48] The highest mutation rate in MPM cases was found in the northern regions of Italy, particularly in Liguria and Lombardy, followed by Veneto (35%, 24%, and 12%, respectively), whereas the percentage decreased in central regions, although remaining near 10% (Fig 2). When family history was taken into account, we observed that the prevalence of CDKN2A mutations in patients with MPM was as high as 44.4%.…”
Section: Resultsmentioning
confidence: 96%
“…44 The other mutations were described with evidence of pathogenicity. [45][46][47][48] The highest mutation rate in MPM cases was found in the northern regions of Italy, particularly in Liguria and Lombardy, followed by Veneto (35%, 24%, and 12%, respectively), whereas the percentage decreased in central regions, although remaining near 10% (Fig 2). When family history was taken into account, we observed that the prevalence of CDKN2A mutations in patients with MPM was as high as 44.4%.…”
Section: Resultsmentioning
confidence: 96%
“…INK4A lead to decreased binding to CDK4 but not CDK6 (35,36), underscoring a predominant role of CDK4 over CDK6 in the development of melanoma. Mutations in CDK4 (R24C) originally identified in melanoma-prone families (28) abolish the interaction with p16 INK4A and, thus, render CDK4 constitutively active (37), further highlighting the importance of CDK4 activation in melanoma.…”
Section: Cdk4 Pathway In Human Melanomamentioning
confidence: 99%
“…The majority of mutations in CDKN2A affect p16 whereas only 2% of at-risk melanoma families have an ARF mutation. 18 Although much is known about this pathway, all of the cross-interactions are not understood. P16 functions to inhibit CDK-4 and keep the retinoblastoma protein in its suppressive state in which it functions to halt the cell cycle 18 (Fig 4).…”
Section: Cdkmentioning
confidence: 99%